Adolescent Idiopathic Scoliosis – Pilot Study on the Application of Extra-corporal Shockwave Therapy (ECSWT) - Hans-Rudolf Weiss; Sarah Seibel; Marc Moramarco (Highlights on Medicine and Medical Research Vol. 11, 2021)
Idiopathic scoliosis is a lateral deviation of the spine of unknown origin. Initiation and progression of AIS may result from vertebral column overgrowth through a lordo-scoliotic maladaptation of the spine to the subclinical (functional) tether of a relatively short spinal cord. Implications for treatment, however have not yet been derived from the findings as published so far with the exception of spinal manipulation described by Tomaschewski or neurosurgical release of the filum terminale as described by Royo-Salvador. Following the rationale of Tomaschewski external manipulation might influence the ‘flatback’ contracture as found in the lower thoracic area in patients with beginning AIS and have a beneficial effect on the 3D deformity of the spine and trunk. The hypothesis for this pilot investigation was that with the application of ECSWT, the ‘flatback’ contracture as commonly found in the lower thoracic area of patients with AIS can be reduced. Materials and Methods: Inclusion criteria for the study were: Girls with a Cobb angle between 20 and 50° (average 35.3°, SD 9.6), age 12 to 15 years (average 14.1years SD 1.1). The methodology included (1) Surface Topography (FormetricÔ Diers) before, (2) after 5 min in the treatment position without application of ECSWT and (3) after the application of ECSWT. Results: Lateral deviation (RMS = Root Mean Square) and Surface Rotation (RMS) both were consistently reduced after the intervention. The sagittal parameters kyphosis angle and lordosis angle both were consistently increased after the intervention. The results were consistent but not significant. Conclusions: The concept of a functional tethering of the spinal cord in patients with AIS is supported by the results from this investigation. The application of ECSWT in patients with AIS seems to have a beneficial influence on 3D deformity and the subjective feeling of a tensed back. Manipulation of the ‘flatback’ contracture as commonly found in the lower thoracic area may be beneficial as pointed out by Tomaschewski.